2002
DOI: 10.1111/1540-6288.00029
|View full text |Cite
|
Sign up to set email alerts
|

Information Flows across Markets: Evidence from China–Backed Stocks Dual–Listed in Hong Kong and New York

Abstract: Using a bivariate generalized autoregressive conditional heteroskedasticity (GARCH) model, we examine patterns of information flows for China-backed stocks that are cross-listed on exchanges in Hong Kong and New York. Results analyzing the dual-listed stocks indicate significant mutual feedback of information between domestic (Hong Kong) and offshore (New York) markets in terms of pricing and volatility. Stocks listed on the domestic market appear to play a more significant role of information transmission in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…This methodology made success to capture interdependencies and spillover mechanisms either in bivariate or in multivariate system. It is worth mentioning that the majority of previous studies have led to the existence of unidirectional and sometimes bidirectional spillovers between international stock markets more amplified in times of financial crises and variant depending on the degree of integration (Gilenko and Fedorova, 2014;Bekiros, 2014;Arouri et al, 2011;Li, 2007;Choudhry, 2004;Darrat and Benkato, 2003;Xu and Fung, 2002;Caporale et al, 2002;Kasch-Haroutounian and Price, 2001;Rigobon, 2001, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This methodology made success to capture interdependencies and spillover mechanisms either in bivariate or in multivariate system. It is worth mentioning that the majority of previous studies have led to the existence of unidirectional and sometimes bidirectional spillovers between international stock markets more amplified in times of financial crises and variant depending on the degree of integration (Gilenko and Fedorova, 2014;Bekiros, 2014;Arouri et al, 2011;Li, 2007;Choudhry, 2004;Darrat and Benkato, 2003;Xu and Fung, 2002;Caporale et al, 2002;Kasch-Haroutounian and Price, 2001;Rigobon, 2001, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For instance Su and Chong (2006) find that for eight Chinese firms listed on both the Hong Kong Stock Exchange (SEHK) and the NYSE the average information share was 89.4% for the SEHK market. Xu and Fung (2002), examining the same market, also found that the majority of information transmission came from the home market (SEHK), while the foreign market (NYSE) was predominantly responsible for volatility spillover. Lieberman, Ben-Zion and Hauser (1999) observe that for a sample of 6 Israeli firms the majority of the price discovery occurs in Israel for all but 1 firm, with the NYSE contributing only a small amount.…”
Section: Literature Reviewmentioning
confidence: 88%
“…The research most closely related to this study is undertaken by Xu and Fung [8], they use multivariate GARCH model and examine the information flow between the Hong Kong and New York stock market. specifically, Kutan and Zhou [9] conduct an empirical study on Chinese ADRs and report that the underlying Hong Kong market has the most significant impact on mean returns of the ADRs, their findings are consistent with those of Kim, et al [2].…”
Section: Literature Reviewmentioning
confidence: 99%